Franchising as a way of reducing moral hazard in the tourism market - Puciato, Daniel; Łoś, Agnieszka; Mrozowicz, Kazimierz (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2013)
The objective of this study was to determine the role of franchising in reducing information asymmetry, and moral hazard arising under this asymmetry between tourism service providers cooperating together. It was indicated that the nature of the tourism market assesses the implementation of franchising as a good solution in this case, and it is expected that the popularity of using franchising as a business model in the tourism sector will increase. Based on the classical static bilateral principal-agent model, the advantages of using contracts that differentiate the remuneration of an agent according to the effort in order to limit the risk of business failure were presented. In the study, the practical implications for drafting franchise contracts in the tourism sector that arise from the implemented model were also proposed
Argumenta Oeconomica, 2013, Nr 1 (30), s. 127-148
Keywords: franchising; information asymmetry; moral hazard; principal-agent model; tourism market; asymetria informacji; pokusa nadużycia; rynek turystyczny